The challenges faced by managers in managing community projects in Modimolle local Municipality of Limpopo Province - Mashangwane, Maruping Ephraim (University of Limpopo, 2013)
Recent changes in Modimolle Local Municipality have placed new external pressures and challenges on project managers change their ways of managing community projects in their sphere of operation. The above challenges had necessitated the researcher to investigate the challenges faced by managers in managing community projects in Modimolle Local Municipality of Limpopo Province. The management of community projects in Modimolle Local Municipality is fraught with challenges such as financial resources, lack of focus on economic development, improvement of livelihood, community participation, sustainability, delegation and also not adhering to Public Financial Management Act and Municipal Financial Management Act. To understand the total context of the challenges faced by managers in managing community projects, an in-depth study of this problem was done by means of relevant literature review, empirical study and variety of other suitable research techniques. Data was collected by means of questionnaires and semi-structured interviews, from project managers who had an experience of community work in the area of the study. The studies have revealed that the management of community projects is not determined by one factor. It emerged that there are various factors that prohibit managers to manage community projects in their sphere of operation, hence the recommendations for improvement stated in chapter five.
Thesis (M.DEV.) --University of Limpopo, 2013
Keywords: Community projects; Modimolle Local Municipality; Limpopo Province; Community management; Community development -- Limpopo Province -- South Africa; Project management -- Evaluation